Growth and relationship of live weight to body measurements in semi-domesticated reindeer (Rangifer tarandus tarandus L.) - Nieminen, Mauri; Petersson, Carl Johan (Rangifer, 1990)
Estimation of live weight from measurements of body dimensions is useful in many management activities with domestic animals. In present study live weight was measured from 2932 female and 1037 male semi-domesticated reindeer (Rangifer tarandus tarandus L.) during different seasons in 1969-85. The age of reindeer varied between 1 day and 14 yrs. Back length (along back from second spinous process to base of tail) and chest girth (just behind front legs) were taken also from 1490 female and 510 male reindeer. The growth of reindeer from birth to adulthood was cumulative consisting of a rapid weight accretion during summers followed by a weight loss or stasis during winters. The mathematical analyses of the growth based on exponential solutions gave average values for growth of female and male reindeer. Body weight of females increased until the age of 4.5 yrs and that of males until the age of 5.5 yrs. During winter and spring body weight of hinds decreased 10 to 15 kg and that of stags 30 to 50 kg in different age groups. Significant linear regressions were found between live weight and back length (r = 0.809 and 0.892), live weight and chest girth (r = 0.860 and 0.872) and live weight and combined body measure (back length + chest girth) (r = 0.877 and 0.941) and live weight and body volume (r = 0.905 and 0.954, respectively) in female and male reindeer. Exponential regressions gave, however, the best estimations of live weight with combined body measure.